2016
DOI: 10.18026/cbusos.00288
|View full text |Cite
|
Sign up to set email alerts
|

Hemşi̇releri̇n Karanlik Ki̇şi̇li̇k Özelli̇kleri̇ni̇n Sosyo-Demografi̇k Deği̇şkenler Açisindan İncelenmesi̇

Abstract: The aim of this study is to determine dark personality characteristics of nurses and reveal whether the evaluations concerning dark personality sub-dimensionsdifferentiate according to individual and demographic characteristics or not. The population of study included all nurses in a public hospital at Ankara. The sample is not selected in the study, and the researchers tried to reach the whole universe and a total of 244 usable responses were obtained. As a result of this study, it is observed thatthere are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The characteristics of granting privilege to people who have advantages for him/her, being a part of the successes that do not belong to him/her, avoiding responsibility in case of constituting a mistake outweigh in a toxic leader whose self-interest dimension is high. Selfishness is explained as nurse leader's decreasing of threat that will come from rivals and subordinates prioritizing his/her own interest (19) . Finally, negative spiritual state is the situations which can reflect on the nurse leader's tone of voice/volume, and determine atmosphere of the working environment (15,20) .…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of granting privilege to people who have advantages for him/her, being a part of the successes that do not belong to him/her, avoiding responsibility in case of constituting a mistake outweigh in a toxic leader whose self-interest dimension is high. Selfishness is explained as nurse leader's decreasing of threat that will come from rivals and subordinates prioritizing his/her own interest (19) . Finally, negative spiritual state is the situations which can reflect on the nurse leader's tone of voice/volume, and determine atmosphere of the working environment (15,20) .…”
Section: Introductionmentioning
confidence: 99%
“…Especially since 2010, the dark triad has begun to be intensively researched in the international literature (Koopman et al, 2016;Volmer et al, 2016;Walsh & Arnold, 2020;Liang et al, 2021). However, the number of studies on this subject in the national literature is quite limited (Kanten et al, 2015;Aydoğan & Serbest, 2016;Özer et al, 2016;Özsoy & Ardıç, 2017;Serbest, 2018;Güler & Kerse, 2019;Güllü & Yıldız, 2019;Özsoy, 2019;Özsoy & Ardıç, 2020;Serbest, 2022;Sökmen & Serbest, 2022;Ayata, 2022;Özgan, 2022). For this reason, it is important to investigate the dark triad in order to better understand the role of differences in corporate employees.…”
Section: Extended Summarymentioning
confidence: 99%
“…When we look at the literature on the subject, limited research has been found in the national literature on the dark triad in the health sector (Özer et al, 2016;Serbest, 2022;Sökmen & Serbest, 2022;Ayata, 2022;Özgan, 2022). Therefore, the research is important and will be beneficial to the literature.…”
Section: Extended Summarymentioning
confidence: 99%
“…Consisted of Machiavellianism, narcissism and psychopathy, Dark Triad concept aroused significant interest and subjected to numerous studies especially in the fields of psychology, organizational behaviour, leadership and management within the last decade (Aydoğan et al, 2017;Ekizler and Bolelli, 2020;Harms and Spain, 2015;Kanten et al, 2015;Özer et al, 2016;Özsoy and Ardıç, 2017). Results showed existence of common underlying elements of Dark Triad (Furnham et al, 2013), which are asserted to be low agreeableness, callousness, lack of empathy, self-promotion, coldness, duplicity, short term orientation, malevolence and egocentrism (Paulhus and Williams, 2002;Wisse and Sleebos, 2016).…”
Section: Dark Triadmentioning
confidence: 99%